Pengembangan E-Karem (E-Katalog Jalur Rempah) Berbasis Carrd Materi Jejak Jalur Rempah di Saparua Maluku untuk Kelas XI SMA Negeri 1 Batu - Wahyuda, Sya'fa Nabila Kurnia; Sulistyo, Wahyu Djoko (Universitas Hamzanwadi, 2024)
Media has become a strategic element in the learning process. The utilization of instructional media must be varied and keep up with technological advancements. The digitization of media in the Society 5.0 era is not merely a trend but a tactical effort to enhance participation in reading and accessing information. Considering the importance of media, this study aims to develop E-Karem, a Carrd-based learning media, and to evaluate its effectiveness and feasibility in education. The content focuses on the spice trade route in Saparua, Maluku. The development of this media follows the Research and Development (R&D) method by Sugiyono. The product validation was conducted by media and subject matter experts, followed by product trials and usage testing. The subjects of this study were 33 students of class XI-10 at SMA Negeri 1 Batu. The results of the study showed that the E-Karem media provided an enjoyable learning experience and was effective in improving students' understanding of the spice trade route in Saparua as a history learning resource.